A Case of Successfully Treated Rhinocerebral Mucormycosis: Dental Implications - Nikolaos Papadogeorgakis; Eleni Parara; Vassilios Petsinis; Christina Vourlakou (International Journal of Dentistry)
This paper presents a case of rhinocerebral mucormycosis in a 22-year-old female patient with type I diabetes mellitus, who was successfully treated with surgery and long-term antifungal medication. The patient had initially been submitted to extraction of an upper third molar by a general dental practitioner but was referred to our department three days postoperatively because of double vision. Immediately following histopathological confirmation of the infection, the patient was administered Amphotericin B and Posaconazole intravenously. Surgical excision of the affected site was relatively conservative. The patient was free of the disease 15 months after initial admission to the hospital and has recently returned for reconstruction. The aim of this paper is to increase the awareness of general dental practitioners regarding uncommon serious conditions in diabetic patients, which may be confused with periodontal or dental diseases.